Teatro do Oprimido: conflito e memória no espaço cênico - Rodrigues, Anderson Zotesso (2012)
The present essay intends to establish connections between the Theater of the Oppressed (TO) as systematized by the Brazilian dramatist Augusto Boal and three categories of mnemonic registering: the “cultural memory” (LOTMAN, 1998) and some of its mass media components, the memory of  oppressions as lived by the authors/actors and transposed to the scenic space, and the memory of Boal himself as presented in his bibliography. As an introduction, some conceptual basis were displayed in order to delimit the investigation field of this study.